Divo Barsotti: Man, God, and Christ in Dostoevsky’s Works - Caterina Corbella (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The article discusses the book by fr. Divo Barsotti “Dostoevsky. The Passion for Christ”. It carries a research project on the interpretation of F.M. Dostoevsky’s works by Catholic religious thinkers and theologians started in 2019. On the one hand, these analyses allow us to discover new ways of interaction between literature and theology, while highlighting Dostoevsky’s, although indirect, contribution to the change of the Catholic world after the second Vatican Council. The article presents the book, its structure, and main contents, and attempts to identify the peculiarities of Barsotti’s reception of Dostoevsky’s texts. Attention is focused on the concept of moral law as an evidence of the existence of God, and on the interpretation of Dostoevsky’s “profession of faith” and, consequently, on who Christ is for Barsotti and Dostoevsky.